2021
DOI: 10.1308/rcsann.2020.7151
|View full text |Cite
|
Sign up to set email alerts
|

The Moondance Bowel Cancer Project schools initiative

Abstract: Background The 5-year survival rate for bowel cancer in Wales is poor and lags behind the rest of the UK. The aim of the pilot phase of the Moondance Schools Initiative was to develop, deliver and assess a bowel cancer learning module for secondary school students in South Wales. Ultimately, we aim to introduce this programme into the National Curriculum across Wales. Methods Two programmes regarding bowel cancer and screening were designed and delivered to a cohort of secondary school pupils in South Wales. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Twenty-two studies used LCHEE for awareness interventions ( Boutsicaris et al, 2021 , Miguel et al, 2020 , Portilla-Skerrett et al, 2019 , Molina et al, 2018 , Holt et al, 2019 , Maxwell et al, 2019 , Maxwell et al, 2020 , Jenkins et al, 2022 , Molokwu et al, 2017 , Warner et al, 2019 , Dominic et al, 2020 , Gray et al, 2021 , Ou et al, 2019 , Tong et al, 2017 , Woodruff et al, 2017 , Mojica et al, 2016 , Parker et al, 2021 , Cassel et al, 2020 , Jo et al, 2017 , Nguyen et al, 2017 , Cuaresma et al, 2018 , Lucas et al, 2021 ). Nineteen studies showed improvements although, the findings of three were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-two studies used LCHEE for awareness interventions ( Boutsicaris et al, 2021 , Miguel et al, 2020 , Portilla-Skerrett et al, 2019 , Molina et al, 2018 , Holt et al, 2019 , Maxwell et al, 2019 , Maxwell et al, 2020 , Jenkins et al, 2022 , Molokwu et al, 2017 , Warner et al, 2019 , Dominic et al, 2020 , Gray et al, 2021 , Ou et al, 2019 , Tong et al, 2017 , Woodruff et al, 2017 , Mojica et al, 2016 , Parker et al, 2021 , Cassel et al, 2020 , Jo et al, 2017 , Nguyen et al, 2017 , Cuaresma et al, 2018 , Lucas et al, 2021 ). Nineteen studies showed improvements although, the findings of three were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five studies used LCHEE for screening education ( Boutsicaris et al, 2021 , Miguel et al, 2020 , Portilla-Skerrett et al, 2019 , Molina et al, 2018 , Holt et al, 2019 , Maxwell et al, 2019 , Maxwell et al, 2020 , Warner et al, 2019 , Dominic et al, 2020 , Gray et al, 2021 , Ou et al, 2019 , Rafie et al, 2020 , Elder et al, 2017 , Tong et al, 2017 , Woodruff et al, 2017 , Maxwell et al, 2016 , Leone et al, 2016 , Christy et al, 2020 , Mojica et al, 2016 , Parker et al, 2021 , Jo et al, 2017 , Nguyen et al, 2017 , Cuaresma et al, 2018 , Sizer and Conyers, 2022 , Champion et al, 2018 ). Ten studies reported screening intentions ( Boutsicaris et al, 2021 , Miguel et al, 2020 , Portilla-Skerrett et al, 2019 , Molina et al, 2018 , Maxwell et al, 2019 , Warner et al, 2019 , Dominic et al, 2020 , Gray et al, 2021 , Mojica et al, 2016 , Parker et al, 2021 ). Six of those reported improvements ( Miguel et al, 2020 , Molina et al, 2018 , Warner et al, 2019 , Woodruff et al, 2017 , Gray et al, 2021 , Parker et al, 2021 ) and three reported no change ( Boutsicaris et al, 2021 , Portilla-Skerrett et al, 2019 , Mojica et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations